Social support as a moderator of the effects of self- and environmental exploration on career choice among beauty education students - Fadhila Fitri Hamdani; Jonni Mardizal; Yuliarma Yuliarma; Waskito Waskito (Global Econedu, 2026)
Career choice in vocational higher education requires students to understand their personal interests and competencies while navigating a rapidly changing professional environment. This study examined the effects of self-exploration, environmental exploration, and social support on career choice and tested the moderating role of social support among Beauty Education students. A cross-sectional explanatory survey was conducted with 177 fourth-, sixth-, and eighth-semester students selected using proportionate stratified random sampling. Data were collected through a 56-item four-point Likert questionnaire and analyzed using multiple regression, moderated regression analysis, and simple slope analysis. The direct-effect model was significant and explained 36.6% of the variance in career choice. Self-exploration (B = 0.284; β = 0.301; p < 0.001), environmental exploration (B = 0.389; β = 0.382; p < 0.001), and social support (B = 0.157; β = 0.153; p = 0.014) made positive contributions. Adding the interaction terms increased R² to 0.395 (ΔR² = 0.028; p = 0.020). Social support strengthened the effect of self-exploration (B = 0.230; p = 0.028) but attenuated the positive effect of environmental exploration (B = -0.242; p = 0.013). Career development programs should therefore combine structured self-reflection, professional-environment exposure, and autonomy-supportive social resources